Bioremediation of hexachlorocyclohexane (HCH) in soil using spent mushroom compost of Pleurotus ostreatus. Issue 3 (2nd October 2018) - Sadiq, Saima; Mahmood-ul-Hassan, Muhammad; Ahad, Karam; Nazir, Sehrish
Abstract: Hexachlorocyclohexane (HCH), a highly chlorinated pesticide, was used worldwide in the 1950s and 1960s. HCH toxic residues are still detected in environmental compartments. Thus, effective, viable and eco-friendly strategy is required for its remediation. In this study, degradation of four HCH isomers was evaluated by amending contaminated soil using four treatments of spent mushroom compost (SMC) of Pleurotus ostraetus . The soil was incubated for 5 weeks and was sampled every seven days. Quantitative attenuation in HCH was calculated using gas chromatography–electron capture detector (GC-ECD) and metabolite was identified using gas chromatography–mass selective detector (GC-MSD). Maximum reduction 58%, 26%, 45%, and 64% for α-, β-, γ- and δ-HCH isomers, respectively, using SMC and soil (both unsterilized) showed that this treatment was the best for bioremediation of HCH in soil. However, when one of the factors, either soil or SMC, was sterilized, a significant reduction in HCH degradation was noticed. The second most reduction of isomers was seen during treatment where unsterilized SMC was added in sterilized soil followed by treatment where SMC was sterilized but soil was not. Abiotic control did not remove any significant quantities of HCH. Simple first-order (SFO) kinetic confirmed that SMC reduced the half-live manifolds as compared to biotic control. Only one metabolite δ-PCCH was identified during the course of study.